Studi Analisis Skema IBE-ECC pada Komunikasi Data Mobile Application - Salim 'Imaduddiyan (Journal on Education, 2023)
Environmental science is one of the new fields of science. This science was born in response to changing environmental conditions that are increasingly concerning. Environmental science has been studied in various colleges in different parts of the world. As a new science, environmental science has different positions in universities with various statuses ranging from courses, majors, study programs, departments, faculties to schools. Studying environmental science will also be closely related to the concept of sustainable development. But this all needs to be explored and studied more deeply about its development and role. The purpose and objective of this study is to know, describe and analyze the development and role of environmental science through higher education and its contribution in developing the concept of sustainable development, especially in Indonesia. The method used in this research is through a desk study. The results of temporary research show that environmental science has developed along with and in accordance with global environmental conditions. Universities both in the world and in Indonesia have taught environmental science, even becoming one of the sciences that are in demand and developing today. In addition, environmental science has an important role in contributing its thoughts to Indonesia and the world and to achieve sustainable development